Influence of Slope Aspects and Depth on Soil Properties in a Cultivated Ecosystem - Akbari, Abolghasem; Azimi, Rehayne; Noram Irwan, Ramli (EJGE, 2014)
In order to find out how topographical factors effect on soil properties, as a pivotal indicator in terms of soil degradation and sustainable land management in natural ecosystem, the investigation of soil physical and chemical parameters are indispensable. The research aimed to assess slope aspects on soil quality. Soil samples were gathered by completely randomized factorial design in four geographical directions and flat by three replications in two depths of 0-30 and 30-60 cm; therefore equals 30 soil samples from the dry and irrigation farming of Khorasan Razavi. The investigated variables were Total Nitrogen, Phosphorus, Potassium, pH, Saturated Percentage, Calcium Carbonate Equivalent, Fe and Soil Texture. Results showed that there was a significant relationship in N, P and F, whereas there was no significant relationship in K, pH, SP and TNV in different aspects. Turning to depths, none of parameters showed statistically significant, except for P. Totally, the results suggest that West and Flat aspect are the appropriate area for agriculture. The differences may be attributed to topographic aspect, which causing differences in the some soil component, affect soil fertility